2014
DOI: 10.1007/s11524-014-9924-1
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine Maintenance Treatment Retention Improves Nationally Recommended Preventive Primary Care Screenings when Integrated into Urban Federally Qualified Health Centers

Abstract: Buprenorphine maintenance therapy (BMT) expands treatment access for opioid dependence and can be integrated into primary health-care settings. Treating opioid dependence, however, should ideally improve other aspects of overall health, including preventive services. Therefore, we examined how BMT affects preventive health-care outcomes, specifically nine nationally recommended primary care quality health-care indicators (QHIs), within federally qualified health centers (FQHCs) from an observational cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 66 publications
2
56
0
Order By: Relevance
“…A prior study of patients with OUD in federally qualified health centers who were initiating buprenorphine treatment found that receiving buprenorphine from a primary care physician rather than a psychiatrist and being retained in buprenorphine treatment were both associated with higher rates of nationally recommended preventive health care screening. 23 These findings emphasize the important role that primary care can play in improving treatment for patients with OUD. While the idea of increased visit frequency may be daunting, team-based care offers an effective and efficient model.…”
Section: Discussionmentioning
confidence: 92%
“…A prior study of patients with OUD in federally qualified health centers who were initiating buprenorphine treatment found that receiving buprenorphine from a primary care physician rather than a psychiatrist and being retained in buprenorphine treatment were both associated with higher rates of nationally recommended preventive health care screening. 23 These findings emphasize the important role that primary care can play in improving treatment for patients with OUD. While the idea of increased visit frequency may be daunting, team-based care offers an effective and efficient model.…”
Section: Discussionmentioning
confidence: 92%
“…The C&C also received high satisfaction ratings for reducing drug craving (often associated with relapse) and for promoting better family relationships. Though reported satisfaction levels were highest specifically for addiction treatment, the high levels of medical and psychiatric comorbidity suggest the need to integrate more comprehensive services into the C&C in order to optimize health outcomes (Bachireddy et al, 2014; Haddad, Zelenev, & Altice, 2015; Sylla, Bruce, Kamarulzaman, & Altice, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Because opioid use disorders are chronic and relapsing, long-term retention in OAT is crucial to meet recovery needs to decrease drug use and relapse, and improve social functioning, quality of life, and reduced mortality (Bart, 2012; De Maeyer, van Nieuwenhuizen, Bongers, Broekaert, & Vanderplasschen, 2013; Korthuis, Tozzi, et al, 2011; Nosyk, 2011; Timko, Schultz, Cucciare, Vittorio, & Garrison-Diehn, 2015). OAT retention has also been associated with improvements in addressing primary care (Haddad, Zelenev, & Altice, 2013, 2015) and HIV treatment outcomes (Altice et al, 2011; Korthuis, Fiellin, et al, 2011). …”
Section: Introductionmentioning
confidence: 99%